Implementation of Good Corporate Governance Principles in Improving the Performance of State-Owned Enterprises in Indonesia: Penerapan Prinsip Good Corporate Governance Dalam Meningkatkan Kinerja BUMN di Indonesia - Anisa Paujiah Sinaga; Mursal Amri Harahap; Vingkan Andini; Zahra Fatin Miera; Ahmad Wahyudi Zein (CV. KAMPUS AKADEMIK PUBLISING, 2025)
State-Owned Enterprises (SOEs) play a strategic role as agents of national economic development, but often face challenges related to transparency, weak oversight, and potential abuse of authority that hinder optimal performance. This study aims to analyze the urgency, implementation, and impact of implementing Good Corporate Governance (GCG) principles in optimizing the value and competitiveness of SOEs. GCG is a corporate management system based on the principles of transparency, accountability, responsibility, independence, and fairness (TARIF). The study results show that GCG implementation not only improves operational efficiency and investor/public trust but also effectively minimizes the risk of conflicts of interest. SOEs need to build a GCG culture through three main pillars: people, systems, and structure. In conclusion, GCG must be the main foundation of SOE management so that state-owned companies are able to make maximum contributions to the welfare of the Indonesian people.